Development and evaluation of a tailored mHealth parenting program for multicultural families: a three-arm cluster randomized controlled trial - Son, Hyunmi; Han, Gyumin (Frontiers in Public Health, 2023)
Objective Health management of children during early childhood requires substantial information. Multicultural families find it difficult to obtain and use parenting-relevant information for their young children. This study aimed to develop, implement, and evaluate a tailored Health parenting program and lay-health workers’ support to improve children’s health in multicultural families in Korea. Methods In this study, we employed the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model as the conceptual framework, guiding the creation of a tailored mHealth application supplemented by a lay-health worker support module. The efficacy of the program was assessed through an experimental three-arm cluster randomized controlled trial. A total of 101 participants were stratified into three distinct groups as follows: (1) Experimental Group A, which received the mHealth program alongside the lay-health worker support component; (2) Experimental Group B, exposed solely to the mHealth program; and (3) Control Group, devoid of any intervention. Within these groups, 101 marriage migrant women hailing from Vietnam, the Philippines, and China were incorporated, with each group comprising 33, 30, and 38 participants, respectively. The study’s primary endpoint encompassed a comprehensive assessment of health-promoting behaviors, proficiency in eHealth literacy, and the family strength. Results The analysis revealed noteworthy interactions among the three distinct groups over the course of time, with implications for health-promotion behaviors (p = 0.041), eHealth literacy (p = 0.037), and family strength (p = 0.044). Specifically, the experimental groups exhibited substantially elevated levels of the specified outcome variables when contrasted with the control group. Notably, the positive effects persisted even up to 12 weeks subsequent to the conclusion of the intervention, underscoring the program’s capacity to foster enduring improvements in the observed metrics. Conclusion This study highlights the benefits of offering contextually appropriate information to target groups constrained by challenges in information access, evaluation, and utilization. Notably, drawing from their positive experiences in this process, we underscore the importance of employing lay health workers. These workers play a crucial role in fostering and ensuring sustained behavioral changes.